Assessing the Validity of an English E-Module Incorporating Local Wisdom and the Pancasila Student Profile - Destiani Rahmawati; Yudi Juniardi; Hidayatullah; Ike Hilatun Nisa (Side: Scientific Development Journal, 2025)
The objective of this research is to create a learning medium in the form of an E-Module based on local wisdom, incorporating values related to local wisdom, the environment, and community technology, as well as integrating the Pancasila Student Profile, making it suitable to serve as an English teaching module for junior high school students. The research methodology employed is development research, utilizing Thiagarajan’s 4-D model, which progresses through the stages of Define, Design, Development, and Dissemination. The instruments used include expert validation sheets and material validation sheets, consisting of four material aspects with 15 questions and three media aspects with 13 questions; the validation results are analyzed using a percentage formula and then converted. Based on the validation outcomes, the English E-Module based on local wisdom and containing the Pancasila Student Profile is considered suitable for use as teaching material. Specifically, the validation by media experts indicates that the E-learning module is highly feasible, with a percentage of 93,8 %. Furthermore, validation by experts in English material and the Strengthening of the Pancasila Student Profile also confirms the feasibility of the E-module, with a percentage of 85.3%, resulting in an overall average validation score of 89.55%. From these findings, it can be concluded that this E-Module, which is based on local wisdom and contains the Pancasila Student Profile, is highly suitable for use as English teaching material for Grade VIII students at SMP N 8 Tangerang City.